INVESTIGATING THE EFFICACY OF U-DICTIONARY APP FOR IMPROVING STUDENTS’ VOCABULARY MASTERY - Fiqri, Diqi Ahsanul; Sofiana, Nina (English Review: Journal of English Education, 2024)
The objective of this study is to assess how well the U-Dictionary app enhances the English vocabulary skills of 10th-grade students at SMK Al-Haromain. This research employs a Quasi-Experimental approach, which includes two groups: an experimental group and a control group. The participants in this research were students from class X TKJ assigned to the experimental group, while students from class X TBSM were assigned to the control group. The data collection tool consists of a Pre-test and Post-test, which includes a total of 20 valid multiple choice questions. The researcher utilized the independent sample t-test feature in the SPSS software to verify the accuracy of the hypothesis. The mean post-test value in the experimental class was 87.6, while in the control class it was 72.8, according to the results of the two-tailed independent sample t-test. It can be inferred that the utilization of the U-Dictionary app effectively enhances the vocabulary proficiency of 10th-grade students at SMK Al-Haromain Mayong.